A randomised controlled trial of motivational interview for relapse prevention after release from smoke-free prisons in Australia. Issue 4 (23rd December 2020) - Jin, Xingzhong; Kinner, Stuart Alistair; Hopkins, Robyn; Stockings, Emily; Courtney, Ryan James; Shakeshaft, Anthony; Petrie, Dennis; Dobbins, Timothy; Puljevic, Cheneal; Chang, Shuai; Dolan, Kate
Abstract : Purpose: This paper aims to determine whether a single session of a motivational interview (MI) reduces smoking relapse amongst people released from smoke-free prisons. Design/methodology/approach: This study sought to recruit 824 ex-smokers from 2 smoke-free prisons in the Northern Territory, Australia. Participants were randomised to receive either one session (45–60 min) face-to-face MI intervention 4–6 weeks prior to release or usual care (UC) without smoking advice. The primary outcome was continuous smoking abstinence verified by exhaled carbon monoxide test (<5 ppm) at three months post-release. Secondary outcomes included seven-day point-prevalence, time to the first cigarette and the daily number of cigarettes smoked after release. Findings: From April 2017 to March 2018, a total of 557 participants were randomised to receive the MI ( n  = 266) or UC ( n  = 291), with 75% and 77% being followed up, respectively. There was no significant between-group difference in continuous abstinence (MI 8.6% vs UC 7.4%, risk ratio = 1.16, 95%CI 0.67∼2.03). Of all participants, 66.9% relapsed on the day of release and 90.2% relapsed within three months. On average, participants in the MI group smoked one less cigarette daily than those in the UC within the three months after release ( p  < 0.01). Research limitations/implications: A single-session of MI is insufficient to reduce relapse after release from a smoke-free prison. However, prison release remains an appealing time window to build on the public health benefit of smoke-free prisons. Further research is needed to develop both pre- and post-release interventions that provide continuity of care for relapse prevention. Originality/value: This study is the first Australian randomised controlled trial to evaluate a pre-release MI intervention on smoking relapse prevention amongst people released from smoke-free prisons.